AN ION PROBE STUDY OF ANNUAL CYCLES OF SR/CA AND OTHER TRACE ELEMENTS IN CORALS - Hart S.R.; Cohen A.L. (My University, 1996)
Corals show great promise for preserving century-long records of ocean chemistry and temperature with weekly time resolution. Allison and Tudhope (1992) showed that direct microscale analysis of coral skeletons was possible with ion microprobe techniques. We show here that analysis of B, F, Mg, Sr, and Ba (relative to Ca) can be rapidly achieved on Porites skeleton at 50 μm (sub-weekly) spatial scales with precisions of 0.3-3%.The B, F, and Mg concentrations show large well-behaved annual variations of 44-57%, well-correlated with Sr/Ca variations of 12%, in the 1967-1969 bands from a live Porites from Two-Mile Reef, South Africa. The Sr/Ca ratio correlates well with the δ18O record but shows a larger annual temperature amplitude, with additional numerous sub-weekly temperature spikes. Ba/Ca in recent bands of Porites shows both a large (factor of 5) annual cycle and a large yearly spike in the late summer; the annual variation is not observed in 30-year-old bands, though the annual spikes are still sharp and clear. Barium thus appears to be unstable in Porites during aging and is probably not skeletally-bound.Deep-sea (nonzooxanthellate) corals show uncorrelated variations of these same trace elements, with amplitudes similar to the Porites. These variations are likely biologically-mediated, as the thermal forcing function in the deep sea is nil. This suggests that the annual variations seen in Porites may also be driven by vital effects and not directly by temperature.Ion microprobe techniques are shown to provide rapid, precise, and high-resolution trace-element records in corals. Full exploitation of trace element paleotemperature methods in corals will require a more sophisticated understanding of how corals accrete their skeletal components. Ion probe analysis can contribute significantly to this understanding.